2012
DOI: 10.1016/j.ibmb.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and proteomic studies on the effects of the insect growth regulator diflubenzuron in the model beetle species Tribolium castaneum

Abstract: SUMMARY Several benzoylphenyl urea-derived insecticides such as diflubenzuron (DFB, Dimilin®) are in wide use to control various insect pests. Although this class of compounds is known to disrupt molting and to affect chitin content, their precise mode of action is still not understood. To gain a broader insight into the mechanism underlying the insecticidal effects of benzoylphenyl urea compounds, we conducted a comprehensive study with the model beetle species and stored product pest Tribolium castaneum (red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 86 publications
6
77
1
4
Order By: Relevance
“…S1 B and C). These specific symptoms are nearly identical to those observed with benzoylureas in insects (12). To establish the effect of etoxazole on chitin deposition in mites, we treated synchronized female deutonymphs with etoxazole and collected the teleiochrysalis stage just before ecdysis.…”
Section: Resultssupporting
confidence: 62%
“…S1 B and C). These specific symptoms are nearly identical to those observed with benzoylureas in insects (12). To establish the effect of etoxazole on chitin deposition in mites, we treated synchronized female deutonymphs with etoxazole and collected the teleiochrysalis stage just before ecdysis.…”
Section: Resultssupporting
confidence: 62%
“…Earlier, it has been reported that CHS expression changes of up to two-fold can occur even among control insect samples 17. Further, results from previous studies do not reveal a consistent pattern on the effect of DFB and other Benzoylphenylureas on insect CHS expression 14, 17, 18, 43. DFB has been found to enhance the CHS1 expression in A.quadrimaculatus 14 but not in D. melanogaster 17 and T. casteneum 18.…”
Section: Discussionmentioning
confidence: 85%
“…The three main constituents of the cuticle are proteins, lipids and chitin, the latter chitin, a homopolymer comprising β-(1-4)-linked N-acetyl-D-glucosamine residues, is one of the most abundant, easily obtained and renewable natural polymers, second only to cellulose and it is commonly found in many invertebrates and in the cell walls of most fungi and algae [1][2][3]. In the last few years, research shows that the enzymes in chitin metabolism are the critical target for insecticides [4][5][6].…”
Section: Introductionmentioning
confidence: 99%